The ectopic newly-formed nerve fibres which repopulate the long-time denervated and atrophic chick skeletal muscle - Eros Abrantes Erhart; Cecil José Rezze; Walter Biazotto (Arquivos de Neuro-Psiquiatria)
1. The whole biventer cervicis muscles of the chick, being innervated by a branch of the dorsal ramus of C, presents structural Deculiarities which recommend it as good skeletal muscle for embryological, anatomical, physiological and pharmacological neuro-muscular investigations. 2. The nerve trunk responsible for the innervation of the distal belly runs completely included within the intermediate tendon; therefore, a tendon transection determines complete denervation and nerve fibre degeneration of the distal belly of the muscle. 3. Long-time experimentally denervated distal bellies (from three up to twelve months) are repopulated by ectopic nerve fibres which must have arisen from a source other than the proximal stump, neighbour nerves or nervi-vasorum. 4. Motor endplates appear in these long-time (eight or more months) denervated biventer cervicis distal bellies. 5. Although atrophic-looking such muscle bellies responded to indirect and to direct electrical stimulation — 1.5 V — by contraction. 6. The long-time denervated distal bellies of the biventer cervicis muscle of the chick, when properly reoperated by cross-grafting suture with the normal contralateral muscle, lost their atrophic appearance and showed to be successfully recovered in about thirty days.